Multi dimensional modelling of a high pressure natural gas fuel injection process in prechamber of a single cylinder four-stroke engine - Muhamad Azman, Mohd Yamin (2012)
This thesis deals with the numerical setup of a simulation for compressed natural gas in spark ignition engine with pre-chamber for the full cycle four-stroke engine using Computational Fluid Dynamics (CFD). Single-cylinder Yamaha FZ 150i engine is used as the base line engine design for the simulation. The engine is modified by replacing the pre-chamber at the spark plug hole. This study is focused on the combustion model with different ignition and injection timing. 2000 revolution per minute (rpm) and 500 iterations are set as the tested speed and number of iterations per time step respectively. This simulation is started from intake valve open unt il exhaust valve close as a completed cycle of engine. Turbulence is captured using k-ԑ- realizable model. This simulation is divided in 2 cases. Case 1 is set for study the effect of injection timing while Case 2 is set for study the effect of ignition timing. The injection pressure is set 20 bar and 15° crank angle (CA) of injection period. The injection timing that used are 40° before top dead centre (BTDC), 50° BTDC and 60° BTDC while the ignition timing that used are 20° BTDC, 30° BTDC, and 40° BTDC at the 50° CA BTDC. The predicted maximum pressure due to the injection and ignition timing is 27 bar while maximum temperature is 1200 K. For further simulation, more data from experimental work is needed especially pressure and temperature.